A Prospective Observational Study Ondemographic Profile and Clinical Outcomes of Acutepoisoning Cases in a Tertiary Care Hospital in Southern India - Priyadarshini Varadaraj; Aiswarya M Nair; Vaasanthi Rajendran; Lakshmi Marappa; Santhosh Kumar P; Senthil Narayanasamy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The profile of acute poisoning cases is fast changing in last few years, due to advancements in agriculture, construction, sanitation, cosmetic industry and not the least in pharmacology. The advancements and invention of new chemical agents in these industries have increased the access to wide range of materials with quite varied chemical nature, which is reflected in the profile of acute poisonings.Methods: The study is a prospective observational study for a period of 18 months .The study population included all the patients presenting to the emergency department with history of acute poisoning excluding accidental non-self- poisoning.Conclusion: In the current study, highest proportion of subjects in the overall study group was between 26 to 40 years. The proportion of males and females were almost equal whereas in OPC poisoning group the proportion of males was much higher than females. Majority of the affected population were married, living in urban areas, educated ,belonged to lower class. Highest proportion was constituted by housewives and students .Organophosphorous poisoning was the most common poisoning reported followed by benzodiazepines and rat killer in thestudy.The overall mortality rate in the study was 10.53%.Mortality was highest when the subjects were presented beyond 6 hours. Among the type of poisons OPC poisoning had highest mortality.